Transmission planning by minimizing curtailment of market transactions - Gunnaasankaraan, Harivina (2013)
Congestion in the transmission network prevents execution of the desired market transactions. This results in some of the market transactions having to be curtailed, which translates into a loss to customers. This paper suggests that the decision to expand transmission facilities will depend on the loss sustained by the customer due to curtailment of market transactions vs. cost of installing new transmission facilities over a planning period. Thus, in a power system, the sum total cost of investment to expand transmission facilities and cost of cumulative loss due to curtailment of transactions to all the customers is set up as a minimization problem, which results in optimal transmission expansion needed over a planning period. With this consideration, the Benders decomposition technique is used for transmission expansion planning by taking investment cost as the master problem and loss due to curtailment of market transactions as the slave problem. The Southern Brazil power system is used as a test case where this methodology has been employed.